Application of Economic and Mathematical Methods and Models in Personnel Performance Control Practice in Indonesia (Study Case PT. Harapan Jaya Multibisnis) - Sombolayuk, Gerry Geraldo; Tanjung, Novita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The manufacturing industry is a complex sector that requires control over each of its resources, one of which is human resources. One of the indicators that can be used to control human resources is by calculating productivity efficiency. In this study, productivity efficiency was carried out using the Cobb-Douglass production function approach method on the example of the company PT Harapan Jaya Multibusiness. The results of the analysis showed that during the period January-October 2023 the value of productivity efficiency achieved was 15% which indicated low productivity efficiency. After further investigation of the causes of low efficiency, we found two indicators that are the main causes of low productivity efficiency, namely the t-start value of capital expenditure of -23.9871 and p-value of 87%. The low t-start value indicates that the sales ratio is not directly proportional to the cost of capital invested or the cost of capital investment. At the same time, the high p-value indicates that excess labor is involved in the production process.